Role of aqueous extract of Cynodon dactylon in prevention of carbofuran- induced oxidative stress and acetylcholinesterase inhibition in rat brain - Rai, D. K.; Sharma, R. K.; Rai, P. K.; Watal, G.; Sharma, B. (Cellular and Molecular Biology, 2011)
The present study was designed to investigate the ameliorating effect of aqueous extract of C. dactylon on carbofuran induced oxidative stress (OS) and alterations in the activity of acetylcholinesterase (AChE) in the brain of rats. Vitamin C was used as a positive control. Wistar rats were administered with single sub-acute oral dose (1.6 mgkg-1 b.wt.) of carbofuran for 24 h. The OS parameters such as lipid peroxidation (LPO) and the activities of antioxidant enzymes including super oxide dismutase (SOD), catalase (CAT) and glutathione-S-transferase (GST), and that of AChE were studied in brain. Carbofuran treatment significantly increased the activities of SOD and CAT by 75 and 60%, respectively. It also induced the level of LPO by 113%. In contrast, the activities of GST and AChE were recorded to be diminished by 25 and 33%, respectively. Pretreatment of the rats with aqueous extract of C. dactylon (oral; 500mgkg-1) restored SOD activity completely but CAT activity only partially (7%). Carbofuran induced LPO was moderated by 95% in the brain of C. dactylon treated rats. The observed changes in OS parameters in C. dactylon treated group were comparable to that observed in vitamin C (200 mg-kg-1 b. wt.) treated group. Surprisingly, C. dactylon treatment significantly recovered the activity of AChE to a smilar level as observed in the brain of control group. In contrast vitamin C treatment did not cause significant change in the activity of AChE in carbofuran treated group. There were no noticeable changes in the aforementioned study parameters in the brain of rats receiving C. dactylon and vitamin C, only. The results suggest that the study is extremely important in the context of development of new anticholinestesterase and antioxidant antidotes against carbofuran from C. dactylon.